Diversity of liverworts (Marchantiophyta) in the Bromo Tengger Semeru National Park Area - Marinda Sari Sofiyana (Indonesian Journal of Biology Education, 2022)
The Bromo Tengger Semeru National Park (BTSNP) has a high diversity of habitats, making this area a good habitat for mosses. This study aims to explore the types of epiphytic mosses in the BTSNP. The research was conducted from March to April 2013. Mosses were collected using the transect method and plot sampling. Samples were collected at three different altitudes (< 1000 masl, 1000–2000 masl, and > 2000 masl). Three research plots were made at each location with a size of 50x50 m, with a minimum distance of 500 m between plots. In each plot, five trees with a diameter of 10–30 cm were selected. To maximize information related to species diversity, different tree bark textures were selected (rough and smooth). The diversity of epiphytic mosses in the BTSNP was evident in 44 species (11 mosses and 33 liverworts). The highest moss diversity in the BTSNP was found in the Hypnaceae, Lejeuneaceae, and Plagiochilaceae. The diversity of epiphytic mosses in BTSNP was in the moderate category (1<H'<3).